FORMATION OF INTERCULTURAL COMPETENCE OF LEARNERS IN THE EDUCATIONAL PROCESS - Alimova Dilbar Khalimovna (Journals Park Publishing, 2023)
This article provides methodological recommendations for improving the content of literary education in the formation of intercultural competence of students, patriotic, international feelings, respect for traditions and spiritual and aesthetic heritage of different peoples and civilizations.
Keywords: диалог культур, межкультурное взаимодействие, межкультурная коммуникация, литературные взаимосвязи, общечеловеческие ценности, этико-эстетическое воспитание, патриотизм, интернационализм.